Implemenetation of faclity management in building information modelling (BIM) for post construction - Nur Awadah Syakirah, Abd Khalid (2018)
Facilities management (FM) is a multi-disciplinary services and activities that have integration between people, place, process and technology. In terms of a building or facility, a system of comprehensive and incorporated aspects FM should be generated systematically so that the maintenance, asset and life span management are implemented properly. An integration of Building Information Modelling (BIM) with FM system offers a higher standard platform of system, which functionality of managing buildings, facilities and other fixed assets can be integrated as a digital repository for each building component. BIM can also enhance the cooperation between the various disciplines of work, the ability to manage change and capability to provide full information support and management throughout the life cycle of the building. Building information modelling (BIM) is one of the most promising recent developments in the architecture, engineering, and construction (AEC) industry. In order we used BIM technology, an accurate virtual model of a building is digitally constructed. This model, known as a building information model, can be used for planning, design, construction, and operation of the facility. It helps architects, engineers, and constructors visualize what is to be built in a simulated environment to identify any potential design, construction, or operational issues. Research methodology used in this research is by collecting data from UMP Holdings and create a parameter in Revit Software to identified manual data record with new schedule data application of facility management in BIM. Hence, the purpose of this paper is to discuss the concept and definition of FM with BIM and the implementation between FM and BIM.